Comparison of Femoral Triangle Block in Combination with IPACK to Local Periarticular Injection in Total Knee Arthroplasty - Li, Xiang; Wang, Yuanyuan; Chen, Yancheng; Qian, Jiatian; Li, Shiao; Chen, Song; Fu, Peiliang (The Journal of Knee Surgery, 2022)
Objective This article studied the efficacy of two different analgesic methods after unilateral primary total knee arthroplasty (TKA) to find an effective analgesic method.Methods A randomized, double-blind, placebo, parallel, and controlled study was performed to evaluate the benefits of combining the femoral triangle block (FTB) and the interspace between the popliteal artery and the capsule of the posterior knee (IPACK). Forty patients diagnosed with knee osteoarthritis and underwent unilateral primary TKA with FTB and IPACK were divided grouped into the experimental group, and 40 patients undergoing TKA with intra-articular cocktail analgesic mixture local injection were grouped into the control group. All patients received the patient-controlled anesthesia pump for analgesia at postoperative 48 hours. The main indexes were postoperative knee joint rest and activity pain (visual analog scale) and muscle strength of the affected limb; secondary indexes were anesthetic consumption, total morphine consumption, range of motion, and complications (such as postoperative nausea and vomiting [PONV]).Results There was no significant difference in the general data of each treatment group. Compared with the conventional group, the quadriceps muscle strength of the combined FTB and IPACK group was higher with significant statistical differences after surgery (p < 0.05). At postoperative 2, 6, 12, 24, 48, and 72 hours, active pain was better than in the conventional group (p < 0.05). Resting pain was significantly smaller than the traditional group only at postoperative 2, 6, 12, and 48 hours (p < 0.05). Morphine consumption, anesthetics consumption, and hospitalization time were lower than the conventional group, the difference being statistically significant. There were no significant differences between the two groups in postoperative wound healing, infection incidence, blood pressure, heart rate, rash, respiratory depression, deep vein thrombosis, and urinary retention. There were also no significant differences in PONV (p > 0.05).Conclusion Combining FTB and IPACK significantly increased the quadriceps muscle in patients, together with relieving early pain and reducing the amount of anesthetic consumption at different postoperative intervals.
Keywords: total knee arthroplasty; femoral triangle block; interspace between the popliteal artery and the capsule of the posterior knee; rehabilitation; nerve block